Funding of activities of state veterinary services of Russian Federation Subjects - I. M. Klinovitskaya; M. A. Shibayev; A. K. Karaulov (Ветеринария сегодня)
The due performance by the veterinary service of its assigned functions depends largely on the amount of funding provided for different aspects and types of its activities. The paper presents analysis results for 13 main funded activities of veterinary services in 85 Subjects of the Russian Federation in 2019. All the funded activities were reviewed in relation to three funding sources: the federal budget, the budget of a Russian Federation Subject and extrabudgetary sources. The paper examines funding levels of the Russian Federation Subjects’ veterinary services (against actual funding requirements) with respect to each object of expenditure and each funding source; besides, the share of each funding source in overall funding of the veterinary service of the country on the whole and of certain types of its activities was determined. In 2019, overall funding of the veterinary service of the country amounted to about 49.5 billion rubles which made up 96% of funding requirements for this period. The major sources of funding were the budgets of the Russian Federation Subjects (56.3%) and veterinary services’ own extrabudgetary resources (43.2%). Only 0.5% of all the funds received by the state veterinary service of the Russian Federation were allocated from the federal budget. The following 4 out of 13 analyzed aspects of activities of the Subjects’ veterinary services were fully funded: staff salaries, anti-epidemic activities, the purchase of reagents and test systems, the implementation of monitoring and screening programmes at the Subject level for contagious animal disease control. The funding levels for other activities of the country’s veterinary service were from 9% (accreditation of veterinary laboratories and maintenance of accreditation) to 87% (the implementation of regional monitoring of food product, raw material, animal product quality and safety; animal health awareness-raising and information activities).